PENGARUH SERVICESCAPE DAN SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA PADA MINAT BELI KONSUMEN DI RESTORAN KOTA PONTIANAK - -, MUQIMUDDIN - (Jurnal TIN Universitas Tanjungpura, 2017)
The continued development of the business makes the business of restaurant has been widely spread in Pontianak. This development is shown by the restaurant business in Pontianak is located on the second level after the advertisement tax. Restaurant tax in 2016 can realize 100.48% achievement of revenue target. Along with increase in it, also accompanied by increaseÂ number of restaurant in Pontianak. The existence of these developments eventually suppress the restaurateur to provide a concept of restaurant that can attract public attention. As for satisfaction or customer unsatisfaction will provide feedback in the form of behavior after deciding to buy or not. This research was conducted with the aim of analyzing the influence of servicescape and service quality to customer satisfaction and their purchase intention in the restaurant. Another aim is to prove the influence of customer satisfaction provided by the entire restaurant in Pontianak on consumers' Purchase intention. Structural equation modelling method is used to develop a model based on the theories of experts. Then,can explain the relationship between the variables. The subjects of this research were the consumer restaurants in Pontianak with a sample of 270 people from a total population of Pontianak. The sampling method by Issac and Michael and Maximum Likelihod (ML) were used. Based on the results of this research showed that servicescape has no effect on customer satisfaction with t-critical > 1.96 with a value at significance level of 0.05. While the service quality gave the effect on customer satisfaction. While purchase intention showed it was affected by servicescape, and also demonstrated customer satisfaction with the results of hypothesis testing showed the critical t-critical > 1.96 at significance level of 0.05. But, the service quality does not significantly influence to purchase intention. Keywords: Customer Satisfaction, Purchase intention, Servicescape, Service Quality, Structural Equation Modeling